Impact force and velocities for kicking strikes in combat sports: A literature review - Corcoran, D.; Climstein, M.; Whitting, J.; Del Vecchio, L. (Sports, 2024)
Kicking strikes are fundamental in combat sports such as Taekwondo, karate, kickboxing, Muay Thai, and mixed martial arts. This review aimed to explore the measurement methods, kinematics such as velocities, kinetics such as impact force, determinants, and injury potential of kicking strikes in combat sports. Searches of Academic Search Premier, The Allied and Complementary Medicine Database, CINAHL Plus, MEDLINE, SPORTDiscus, Scopus, and Web of Science databases were conducted for studies that measured kicking velocity and impact force. A total of 88 studies were included in the review. Studies most frequently involved only male participants (49%) aged between 18 and 30 years of age (68%). Studies measuring velocity predominantly implemented camera-based motion capture systems (96%), whereas studies measuring impact force displayed considerable heterogeneity in their measurement methods. Five primary strikes were identified for which foot velocities ranged from 5.2 to 18.3 m/s and mean impact force ranged from 122.6 to 9015 N. Among the techniques analysed, the roundhouse kick exhibited the highest kicking velocity at 18.3 m/s, whilst the side kick produced the highest impact force at 9015 N. Diverse investigation methodologies contributed to a wide value range for kicking velocities and impact forces being reported, making direct comparisons difficult. Kicking strikes can be categorised into throw-style or push-style kicks, which modulate impact through different mechanisms. Kicking velocity and impact force are determined by several factors, including technical proficiency, lower body strength and flexibility, effective mass, and target factors. The impact force generated by kicking strikes is sufficient to cause injury, including fracture. Protective equipment can partially attenuate these forces, although more research is required in this area. Athletes and coaches are advised to carefully consider the properties and potential limitations of measurement devices used to assess impact force.